Enhancing fatigue life by ductile-transformable multicomponent B2 precipitates in a high-entropy alloy - Rui Feng; You Rao; Chuhao Liu; Xie Xie; Dunji Yu; Yan Chen; Maryam Ghazisaeidi; Tamas Ungar; Huamiao Wang; Ke An; Peter. K. Liaw (Nature Communications, 2021)
A fundamental understanding of fatigue-failure mechanisms is key to develop robust structural materials. Here the authors report a high entropy alloy with enhanced fatigue life by ductile transformable multicomponent B2 precipitates, as revealed by combined experimental and simulation methods.